Effects of Remote Education During the COVID‐19 Pandemic on Young Children's Learning and Academic Behavior in Georgia: Perceptions of Parents and School Administrators. (12th April 2022) - Klosky, Jill V.; Gazmararian, Julie A.; Casimir, Olivia; Blake, Sarah C.
ABSTRACT: BACKGROUND: In Spring 2020, Georgia public schools implemented remote learning to manage the spread of COVID‐19. This study explores the effects of remote schooling on the learning of young children in Georgia during the early COVID‐19 pandemic from the perspectives of school administrators and essential working parents. METHODS: A qualitative exploratory study was conducted with eight school administrators and 26 essential working parents of children in kindergarten through third grades of two rural and two urban schools in Georgia. Data collection included online surveys, virtual interviews and focus groups. Descriptive analyses of the demographics provided context to emerging themes from qualitative data. RESULTS: Most school administrators and parents reported declines in student learning and academic behavior related to remote learning. Lack of Wi‐Fi, technology, and digital literacy were often cited as barriers to learning. Challenges with remote learning were amplified for students and parents of vulnerable groups. CONCLUSIONS: The findings of this study illustrate the need to institute policies, procedures, and supports to maximize schools' ability to safely offer in‐person learning during the COVID‐19 pandemic. Considerations should be made of the needs of essential working parents, vulnerable populations, and the digital divide.